Comparative Study of Mechanical and Biological Pretreatment for Releasing Spores of Black Truffle Tuber aestivum - E. V. Malygina; N. A. Imidoeva; A. Yu. Belyshenko; M. E. Dmitrieva; V. N. Shelkovnikova; A. A. Vlasova; T. Yu. Telnova; M. M. Morgunova; A. S. Konovalov; D. V. Axenov-Gribanov (Mycobiology)
It is well known that the number of true truffles in the wild is decreasing. The aim of the study was to develop an effective, simple and affordable method of asci disruption to release black truffle spores. It was shown that the spore release can be achieved by different ways, such as mechanical or biological destruction. Mechanical homogenization of fruiting bodies using an immersion blender in tandem with a ball mill was shown to be effective and led to destruction of at least 85% of asci and release of spores. Also, the first approach we applied was the biological method of spore activation performed by African and grape snails. As a result of digestion of truffle fruiting bodies, the spores not only lost their protective shells, but also changed their morphology, which promoted their germination in vitro. The spores obtained using these two methods are capable of forming mycelial hyphae on nutrient media. The results of our study can be used to prepare inoculum of Tuber spp. and to obtain their pure cultures in agriculture.